Razkrajanje slovenskega srednjega sloja - Kos, Marko (Teorija in praksa, 2011)
The development in transition has stopped due to high levels of unemployment and due to the transformation imposed by globalisation; the middle class has nearly disappeared, leaving only the lower class and a tiny upper class. The society has become impermeable. The consolation about a rebound is not valid. The frustration of the unemployed people holding university degrees is devastating and harmful. The number of the population below the poverty threshold amounts to 411.000, i.e. 20% of the total population. This percentage continues to increase with the growing number of unemployed and with the rise of the minimum cost of living. If the economic situation does not improve, the majority of the population is expected to slide into poverty. A university degree holder cannot expect to gain more than a salary of a successful qualified worker. Cultural workers find themselves in a specific situation, where the conditions have become humiliating. They are either no longer remunerated or the fees have been decreased by 10% compared to previous years. Only 'workers', readers, and translators are remunerated. The publishing companies tacitly assume that the artist's work is a hobby and a social recognition, for which the authors do not need remuneration. The latter have become 'the proletariat of knowledge'.
Keywords: Družbena slojevitost; Social stratification; Srednji razredi; Middle classes; Brezposelnost; Unemployment; Družbena pogodba; Social contract; Social differences; Socialne razlike; Slovenia; Slovenija